How was Environment Reflected in Early Islamic Literature: a Scientific Analytical Study - Muhammed VP (Penerbit Hellow Pustaka, 2025)
The failure of United Nations interventions in maintaining environmental sustainability is evident as measures like the Paris Agreement and Sustainable Development Goals fall short in effectively addressing global environmental challenges. Therefore, it is crucial to mandate environmental ethics and laws for individuals, as collective effort proves more effective in addressing these concerns. This study explores how the environment and its sustainability are defined in early Islamic literature, with a primary focus on the Quran and Hadith (saying, action, or approval attributed to the Islamic prophet Muhammad). These works are considered the foundation of Islamic teachings and Arabic literature. Additionally, the paper examines the debate surrounding the meaning of sustainable development and the policy implications of various approaches from an Islamic perspective. Islam, as a religion, holds a deep sense of respect and consideration for the natural environment (Izzi Dien, 1990), with Islamic environmentalism ingrained within its teachings. Scientifically, this paper delves into how elements of the environment, such as mountains and water bodies, are defined in early Islamic literature, including contemporary poetry. Through a qualitative approach, it highlights the significant importance given to the environment in early Islamic literature. The study concludes that environmental conservation and ecological sustainability were extensively discussed in early Islamic literature, providing a framework for addressing numerous global environmental issues.